(untitled) (MAUSAM, 1966)
Radar observations of monsoon rain over Poona on the lee-side of the Western Ghats have frequently shown the presence of ’melting bands’. On the windward side on the west coast however, the rain echoes generally appear much below the freezing level. The paper describes an unusual observation of a ’melting band’ noticed at Alibag on the west coast of the peninsula during the southwest monsoon.